Experimental and numerical study of the convective mass transfer of solvent in the Expanding-Solvent SAGD process. (1st March 2018) - Meng, Lin; Ji, Dongqi; Dong, Mingzhe; Maini, Brij
Graphical abstract: Highlights: Solvent mass transfer at the steam chamber boundary in ES-SAGD was investigated both experimentally and numerically. The existence of convective solvent movement along the sloping gas-liquid interface was demonstrated. Solvent transverse mass transfers rate increased with increasing permeability liquid flow rate, or a lower fluid viscosity condition. Diffusion and dispersion were found negligible on the transverse mass transfer where gravity-driven convection was the dominate mechanism. Abstract: In the Expanding-Solvent Steam-Assisted Gravity Drainage (ES-SAGD) process, the mass transfer of the dissolved solvent in the steam chamber boundary is critical to the oil production performance. In this study, experimental and numerical simulation approaches are used to investigate the gravity-driven convective movement of solvent in the steam chamber boundary in ES-SAGD. The experiments are conducted in a two-dimensional (2-D) sandpack model, in which a sloping gas-liquid interface in a closed system is developed as an analog of the steam chamber boundary in ES-SAGD. Thus, the flow along the sloping gas-liquid interface is used to represent the flow in the steam chamber boundary in ES-SAGD. Solvent mass transfer is observed by its concentration variation in the direction perpendicular to the flow surface. Later, CMG STARS is used as the simulator to execute the numerical simulations, and the simulation successfully captured the experimental results. In this study, the findings demonstrate the existence of convective solvent movement along the sloping gas-liquid interface. Furthermore, the results show that there is accelerated solvent movement along the interface under high permeability, and slow movement along the interface under high flow rate and high fluid viscosity. Diffusion and dispersion are tested by varying the corresponding coefficients in the physical and numerical models, and results show that these phenomena have negligible effect on the transverse solvent mass transfer process. This study found that gravity-driven convection is the dominant mechanism of solvent mass transfer in the steam chamber boundary in ES-SAGD.